Moisture Sources for Tropical Cyclones Genesis in the Coast of West Africa through a Lagrangian Approach - Pérez-Alarcón; Sorí; Fernández-Alvarez; Nieto; Gimeno (The 3rd International Electronic Conference on Atmospheric Sciences, 2020)
Atmospheric moisture transport plays an important role in the genesis of tropical cyclones (TCs). In this study, the moisture sources associated with the genesis of TCs in the tropical Atlantic Ocean near West Africa, from June to November in the period 1980–2018, were identified. To detect the location of the TCs geneses, the HURDAT2 database from the National Hurricane Center was used. Additionally, global outputs of the Lagrangian FLEXPART model were used to determine the moisture sources that provided water vapor for the genesis of TCs. This model permitted us to track backward in time the air masses from the genesis region of the TCs and identify regions where air masses uptake moisture before reach the target regions. The results reveal that 18.1% (108 TC) of the total number of TCs that formed in the North Atlantic basin were originated in the region of study. The largest frequency for the TCs geneses was observed in August and September, with each one representing approximately 45% of the total. The transport of moisture associated with the genesis of TCs mainly comes from the east of the North and South Atlantic Ocean, as well as from West Africa and the Sahel region. The patterns of moisture uptake confirmed an interhemispheric moisture transport. Finally, during the El Niño, the moisture uptake is more intense over the Atlantic Ocean close to West Africa around 15 °N of latitude, while during La Niña, the pattern is slightly weaker but covers a wider area over the Atlantic Ocean and the north of Africa.